Differences between grammatical gender and semantic gender in pronominal antecedent retrieval in Brazilian Portuguese - Michele Calil dos Santos Alves (Diacrítica, 2019)
Coreference is a syntactic dependency in which pronouns are bound to previous referents in discourse. Granted that antecedents of anaphors must be retrieved from memory in coreference, the aim of this research is to provide more information on how pronominal antecedents are retrieved, and more precisely to clarify the role of gender cues in pronominal antecedent retrieval when gender morphology is overt. Since Portuguese is a language with visible morphology, speakers of this language are used to rely on agreement cues to process language. The results of two eye-tracking experiments conducted with native speakers of Brazilian Portuguese demonstrated that both binding structural constraints and gender morphological cues are equally important in antecedent retrieval in memory throughout processing. In addition, the results indicated that semantic gender seemed to weigh more in memory than grammatical gender since structurally unacceptable candidates carrying semantic gender caused more interference effects than grammatical gender.